2017
DOI: 10.3390/mi8110336
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence Processes of Droplets and Liquid Marbles

Abstract: The coalescence process of droplets and, more recently, of liquid marbles, has become one of the most essential manipulation schemes in digital microfluidics. This process is indispensable for realising microfluidic functions such as mixing and reactions at microscale. This paper reviews previous studies on droplet coalescence, paying particular attention to the coalescence of liquid marbles. Four coalescence systems have been reviewed, namely, the coalescence of two droplets freely suspended in a fluid; the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 140 publications
0
32
0
Order By: Relevance
“…It is clear to see that the radius of liquid neck increased with time following a certain power scaling law with a power exponent ranging from 0.3815 to 0.4564, namely ∝ 0.3815~0.4564 , which is similar to the coalescence behaviour of bare droplets. 10,[33][34][35][36][37] After coalescence, the merged LM oscillated and slowly evolved to its equilibrium shape. However, the relaxation process of the merged LM will not be discussed in this paper.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear to see that the radius of liquid neck increased with time following a certain power scaling law with a power exponent ranging from 0.3815 to 0.4564, namely ∝ 0.3815~0.4564 , which is similar to the coalescence behaviour of bare droplets. 10,[33][34][35][36][37] After coalescence, the merged LM oscillated and slowly evolved to its equilibrium shape. However, the relaxation process of the merged LM will not be discussed in this paper.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…[7][8][9] However, LM coalescence is one of the most essential manipulation schemes to realise microfluidic functions such as microreaction and micromixing in digital microfluidics. 10 A number of coalescence techniques for LMs have been reported in last two decades. Dorvee et al first reported that two liquid droplets encapsulated by magnetic amphiphilic particles can be manipulated using a magnet and coalesce to perform a reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Moving the marble around induces internal flow and promotes mixing. Furthermore, two or more LMs containing different contents can be actuated to collide and coalesce to initiate mixing and reaction [20]. Besides, magnetic LMs [21][22][23][24] can be manipulated to implement multiple microfluidic functions such as reaction and detection.…”
Section: Introductionmentioning
confidence: 99%
“…We have successfully demonstrated the use of dielectrophoretic (DEP) force to move sessile [29,30] and floating LMs [31] in a nonuniform electric field. These manipulation schemes allow for dispensing, merging, trapping, and mixing droplets and LMs [20]. Among these tasks, trapping of droplets and LMs is one of the most important tasks in DMF.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent technique for LM coalescence proceeds through the collision of floating LMs. 24 Floating LMs can be self-propelled or have their movement externally influenced. Selfpropelled LMs usually exploit the Marangoni effect by modifying the surface tension of the supporting medium near the LM via gaseous diffusion of the LMs core.…”
Section: Introductionmentioning
confidence: 99%